Impact of agricultural programs on youth engagement in agribusiness: a case study - Adeyanju, D.F.; Mburu, J.; Mignouna, Djana B. (Canadian Center of Science and Education, 2020)
Using the case of Fadama Graduate Unemployed Youth and Women Support (FGUYS) program, this study assessed the impact of agricultural programs on youth engagement in agribusiness in Nigeria. A total of 977 respondents comprising of 455 participants of the program and 522 non-participants were sampled across three states in Nigeria. Data were analysed using Descriptive and Endogenous Switching Probit Regression (ESPR) Model. The result showed that participation in the program was influenced by age, years of formal education, perception of agricultural programs and type of employment. Furthermore, the results showed a positive impact of the program on youths’ likelihood to engage in agribusiness. The study recommends the need to invest more in agricultural programs such as the case study since it has desirable economic outcome for young people. Also, there is a need to improve the general outlook of agriculture such that it becomes more attractive to young people.